Transitioning from consensual to objective seasonal climate and hydrological forecasting in West Africa and the Sahel - Tanimoune, Laouali I; Assoumana, Boubacar Toukal; Mohamed, Hamatan; Halidou, Tinni Seydou; Ali, Abdou; Kiema, Arsene; Nimon, Pouwereou; Soumana, Djibo; Houngnibo, Mandela C M; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
For nearly fifty years, seasonal climate information has been produced using an expert-based consensual approach during Regional Climate Outlook Forums (RCOFs) such as PRESASS and PRESAGG. While consensual forecasts have been valuable for planning agriculture and disaster risk management in the regions, these forecasts are limited by their low reproducibility, coarse spatial resolution, and reliance on expert judgement. National Meteorological and Hydrological Services (NMHSs) also face persistent structural challenges, including ageing networks, fragmented data systems, limited personnel, and dependence on short-term project funding. To address these gaps, AGRHYMET—endorsed by ECOWAS as a Regional Climate Centre (RCC) for West Africa and the Sahel—has led a major modernization effort in partnership with NMHSs, ACMAD, basin organizations, and international institutions. A new objective seasonal climate and hydrological forecasting system has been developed, with the support of AICCRA project, combining advanced statistical methods, multi-model ensembles, bias correction, and artificial intelligence. Performance evaluation shows significant improvements in accuracy and usability. Capacity building has been central to this transition, including an intensive hands-on training for NMHSs from the 17 countries in the West Africa and Sahel region. A critical step in this modernization effort is the endorsement of the new objective seasonal forecasting systems by the NMHSs Directors, enacting the official transition from consensual to objective approach for seasonal forecasting the region. This report highlighted key insights and shared priorities from the high-level meeting with the NMHSs Directors in West Africa and the Sahel. In addition to the official endorsement of the transition to a new generation of seasonal forecasts produced using the new objective seasonal forecasting systems, the meeting identified shared priorities: strengthening human capacities; modernizing and strengthening observation and information systems; improving data governance; harmonizing methodologies for assessing national water resources. A strong consensus emerged on establishing a regional data-sharing convention aligned with the WMO Unified Data Policy to reconcile national data sovereignty with the need for regional interoperability and integrated early-warning systems. Cross-cutting discussions reaffirmed AGRHYMET’s central role as a WMO RCC and underscored innovation, digitalization, and AI as future pillars of service delivery. Participants stressed the need for long-term national financing, reduced dependency on external projects, and increased inclusion of youth and women in hydro-meteorological careers. Overall, the 2025 high-level meetings with NMHSs Directors marked a turning point in a more coordinated, data-driven, and objective climate and seasonal forecasting system in West Africa and the Sahel, designed to support early warning, policy implementation, and climate-resilient development pathways.